Asymptomatic Embolization After Percutaneous Ostium Primum Atrial Septal Defect Closure: a Rare Complication - Sergiu, Vijiala; Eric, Eeckhout; Grégoire, Girod (Journal of Clinical Case Reports and Images, 2019)
Percutaneous device closure of atrial septal defects (ASD) has proven to be safe and it is nowadays the standard treatment for ASDs. Immediate or late device embolization is a rare but potential complication of every attempted ASD device closure. We report a case of asymptomatic Amplatzer Septal Occluder into the left ventricular outflow tract (LVOT) detected by routine transthoracic echocardiography 3 months after successful implantation in a stable patient.
Keywords: interventional cardiology; cardiology reports; cardiovascular imaging; Ostium Primum Atrial Septal Defect; percutaneous Ostium Primum Atrial Septal Defect closure